Mali : Seventh Review Under the Extended Credit Facility Arrangement, and Request for Extension and Augmentation of Access-Press Release; Staff Report; and Statement by the Executive Director for Mali. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Mali's Seventh Review Under the Extended Credit Facility Arrangement, and Request for Extension of Augmentation of Access. Program implementation is broadly satisfactory but the external position remains difficult and fiscal challenges are mounting. All December 2016 quantitative targets were met. Delays were recorded in the implementation of structural reforms but the authorities have since taken corrective measures. For 2017, expenditures will exceed previously programmed levels to address new security needs as well as costs associated with the decentralization. The IMF staff supports the authorities' request for an augmentation of access equivalent to 13.6 percent of quota in 2017 and extension of the program through 2018.